URBAN MUSLIM YOUTH, PENGAJIAN COMMUNITIES AND SOCIAL MEDIA: FRAGMENTATION OF RELIGIOUS AUTHORITIES IN INDONESIA - Eko Saputra; Dony Arung Triantoro; Ardiansyah Ardiansyah (Al-Qalam, 2021)
Departing from a thesis that states the development of communication technology encourages religious practices among Muslim communities in general, this paper seeks to discuss the fragmentation of religious authority among Muslim youth in Indonesia. The research was conducted through field research. The data were taken from interviews, observation, and documentation. This research showed that the fragmentation of religious authority among muslim youth is motivated by the proliferation of pengajian in Indonesian cities and the use of social media in disseminating da’wah. This research also revealed the involvement of the Indonesian largest da’wah communities that implement youth popular culture in performing pengajian by young ustadz idolized by the young generation. Besides, they also used online media, Youtube and Instagram, to promote their da’wah and even used it as a disseminating media. Hence, this opens up opportunities and facilitates the young generation to instantly gain religious insight without visiting an ustadz or ulama and without becoming a student in an Islamic boarding school